Analysis of Factors Affecting the Human Development Index in Increasing Indonesian Economic Growth in North Sumatra Province - Nur Abda Amalia; Sari Wulandari; Elyyza Cindi Mentari; Indah Mutiara Rizky; Junita Wulandari Dalimunthe (International Journal Labs, 2022)
Background: Improvement can be interpreted as an effort or procedure that can trigger change. This repair procedure covers all aspects of people's lives, including financial, political, social and cultural aspects. Objective: with the aim of achieving financial growth Methods: The methods that can be used are the Pooled Least Square Model (Common Effect), the Fixed Effect Approach Model and the Random Effect Approach Model. Results: The results of data processing show that the t count of the poverty level variable is t count < t table. The significance of the t test is 0.0021 with a significant standard of 0.05, so the significant value of the poverty level is less than 0.05, so Ho is rejected and Ha is accepted. Conslusion: Economic growth has a very positive influence on the HDI in North Sumatra Province, which can be concluded that if increasing economic growth will also increase the human development index in North Sumatra Province because the two are interconnected.